La incidencia de la cultura física en la práctica de la natación de los adolescentes del tercer año de bachillerato de la Unidad Educativa Particular Eloy Alfaro del Cantón Machala, en el período 2012-2013. - Bonilla Silva, Marcelo Andrés (2012)
In any educational center students as well as provide the necessary knowledge, this requires an essential physical health training like mint. There are several natural alternatives that specialized teacher must provide and which have prioritized in the practice of swimming and scientifically, is one of the most complete sports, working and scientifically, is one of the most complete sports , which works both upper- and lower body.